Defect Engineering in Photocatalytic Methane Conversion. Issue 1 (5th November 2021) - Ma, Jun; Long, Ran; Liu, Dong; Low, Jingxiang; Xiong, Yujie
Abstract : With the rapid increase in the discovered reserves of methane, tremendous efforts have been devoted to the conversion of methane into value‐added chemicals. However, current methane conversion technologies require extensive energy consumption (i.e., high temperature and pressure) due to the high stability of methane molecules. Recently, photocatalytic methane conversion has emerged as a potential answer for the above limitation because it can produce reactive intermediates for C—H bond activation by utilizing solar energy as the sole energy input and allow the methane conversion to proceed under mild conditions. Yet, its conversion efficiency remains relatively low mainly due to scarce active sites and rapid photogenerated charge carrier recombination. In this regard, defect engineering, which can create enormous active sites for methane activation and modulate the electronic structure of photocatalyst, has been extensively utilized for photocatalytic methane conversion. In this review, the fundamentals and advantages of various defects along with their preparation strategies are first summarized. Then, recent advances in defect‐mediated photocatalytic methane conversion are highlighted. Finally, the challenges and opportunities on defect‐mediated photocatalytic methane conversion are presented. This review is expected to provide a timely overview of the state‐of‐the‐art development of the defect‐mediated photocatalytic methane conversion toward its practical application. Abstract : This review aims to provide insights into the achievements of photocatalytic methane conversion promoted by defects. The fundamentals of the defects and recent advances in defect‐mediated photocatalytic conversion of methane are first introduced. The challenges and opportunities on the photocatalytic conversion of methane involved defects are also presented to encourage more efficient catalysts for methane conversion.